ANALYSE QUALITATIVE DES REPONSES EPILINGUISTIQUES ET METALINGUISTIQUES AU TEST D’ACCEPTABILITE DU THAM-3 PAR DES ÉTUDIANTS ITALOPHONES - FLOQUET, Oreste (Studia Universitatis Babeș-Bolyai Philologia, 2018)
Qualitative analysis of epilinguistic and metalinguistic answers to the THAM-3 acceptability test by Italian-speaking students. This article as two aims, methodological and descriptive. It analyses the grammatical and metalinguistic judgements of a group of italians learning French (19 adults) elicitated from the acceptability task of the tham 3, a linguistic and metalinguistic tests conceived for native speakers. The goal is to show that some difficulties are due to the structure of these acceptability tasks that influences language proficiency. Finally we comment some interessant results about spontaneous language representation of students learning French as a foreign language. Rezumat. Analiza calitativă a răspunsurilor epilingvistice și metalingvistice la testul de acceptabilitate THAM-3, oferite de studenți italofoni. Obiectivul articolului nostru este dublu. În plan metodologic, mai ales, vom analiza răspunsurile oferite de 19 studenți la un test metalingvistic de acceptabilitate (THAM-3), ce a fost conceput pentru locutori nativi, spre a arăta că o parte a dificultățiilor cu care aceștia se confruntă sunt datorate mai degrabă structurii testului, decât necunoașterii regulilor de gramatică franceză. Într-o a doua etapă, se vor studia și comenta reprezentările metalingvistice ale acestor cursanți din cadrul parcursului FLE. Cuvinte cheie: studiul francezei ca limbă a doua, acceptabilitate, conștiință metalingvistică, lingvistică populară